Pervasive learning using cloud computing - Shah, Asadullah (University of Sindh Jamshoro, Pakistan, 2015)
The popularity and continuously increasing trend in usage of the mobile and handheld devices have dramatically changed the human life style around the entire world. Currently, these devices are also being used in educational sector in general and for the distance learning in particular. Many higher education institutes have adopted distance learning as a means to educate the physically disabled students and those whose physical movement is constrained due to some social or other issues. The distance learning can be provided through various means, however currently one of the emerging methodology of distance learning is Pervasive learning (P-Learning). In contrast to prior distance learning methodologies, such as Electronic Learning (E-learning) and Mobile learning (M-learning), P-learning is getting significant attentions from academic as well as professional researcher's community. Various models and frameworks have been proposed by researchers to adopt P-Learning, however each of them has some tread-offs. In this paper, we have also proposed a model to implement the P-learning system. In contrast to prior work, the proposed model is cost effective and flexible solution to P-learning.